Joint Search by Social and Spatial Proximity [Extended Abstract] - MOURATIDIS, Kyriakos (Institutional Knowledge at Singapore Management University, 2016)
The diffusion of social networks introduces new challengesand opportunities for advanced services, especially so with their ongoingaddition of location-based features. We show how applications like company andfriend recommendation could significantly benefit from incorporating social andspatial proximity, and study a query type that captures these twofold semantics.We develop highly scalable algorithms for its processing, and use real socialnetwork data to empirically verify their efficiency and efficacy.